Pengaruh Pembelajaran Aqidah Akhlak Terhadap Karakter Siswa di Kelas VII MTs Humaira Bojonggede Bogor - Aldiansyah; idhofi, ahmad; Arif Kurniawan, Muchammad (Program Studi Manajemen Pendidikan Islam, 2024)
Educational background is a very important aspect and cannot be ignored in the life of every individual. In the context of faith-based education, Islamic religious education has the aim of communicating the principles of Islamic teachings to mankind. The purpose of this study was to evaluate the learning of aqidah akhlak in students in class VII MTS Humaira Bojong Gede Bogor. This research is a type of quantitative descriptive research, with data collection using questionnaires that focus on learning aqidah akhlak in an effort to shape student character. The study population consisted of 56 respondents, and the entire population was sampled because the number was less than 100. To test the hypothesis, this study used a simple linear regression analysis technique. The results of research on aqidah akhlak learning in class VII Humaira Bojong Gede Bogor, after data analysis was conducted, showed that the average score was 39.803, with a standard deviation of 5.564. The range of values ranges from 21 to 50. Meanwhile, the character building of students in class VII Humaira Bojong Gede Bogor, the results of data analysis showed an average score of 38.803, with a standard deviation of 4.90. The range of values ranges from 22 to 39. It can be concluded that this study shows that there is an influence of aqidah akhlak learning on the character formation of students in class VII Humaira Bojong Gede Bogor, with a significance level of 0.000 which is smaller than 0.05.